Worldview of health and food in the Guambiana culture - Molano-Tobar, Nancy Janneth; Molano-Tobar, Dolly Ximena (Universidad y Salud, 2018)
Introduction: The indigenous culture in Colombia represents a set of historical memories, where their customs reveal the evolution of their own culture, being health and food important aspects from different contexts. Objective: To demonstrate the worldview of health and food processes in the Guambiana indigenous culture. Materials and methods: A qualitative study with an ethnographic approach was conducted with in-depth interview techniques to 12 representatives of the community established by the indigenous Cabildo. Results: The following 3 categories emerged from the investigative process: a) The ancestral culture, our inheritance and pride B) the health mediated by nature C) The feeding focus of survival and change. Conclusions: The Guambiano people manifest a cultural richness that is evidenced from their ancestors in language and clothing, which is a form of identity. In the same sense, health is conceived as the balance of them and nature, which gives them not only the possibility of healing of the diseases from the millennial knowledge of the healers, but also Mother Earth offers them the possibility of feeding and preserving health, despite the linking of external customs.